Cooperative secret delivery in wireless sensor networks. (2nd January 2014) - Deng, Jing; Han, Yunghsiang S.
In the technical literature, many random key pre–distribution techniques have been proposed to secure wireless sensor networks (WSNs). Such techniques only establish keys for some pairs of physically connected sensors. On the contrary, in many WSN applications, a source node must securely communicate with all of its neighbours. In this work, we address the issue of delivering secret link keys to each of the source's neighbours in WSNs. We propose a scheme called cooperative secret delivery (CSD) that finds bridge nodes to deliver keys to the insecure neighbours, which share no prior keys with the source. The novelty of our scheme is to deliver multiple keys through these bridge nodes and regular paths instead of multi–hop secure paths. Since the secret link keys are delivered cooperatively by the bridge nodes in the CSD scheme, secret disclosure probability is significantly lower compared to other delivery techniques. We perform extensive theoretical analysis and performance evaluation on the CSD scheme and demonstrate its salient features.